1998
DOI: 10.1089/neu.1998.15.95
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Moderate Hypothermia on Behavioral Deficits But Not Necrotic Cavitation Following Cortical Impact Injury in the Rat

Abstract: A number of experimental studies have reported that moderate hypothermia can produce significant protection against behavioral deficits and/or morphopathological alterations following traumatic brain injury; a Phase 3 clinical trial is currently examining the therapeutic potential for moderate hypothermia (32 degrees C) to improve outcome following severe traumatic brain injury in humans. The current study examined whether hypothermia (32 degrees C) provided behavioral protection following experimental cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(57 citation statements)
references
References 33 publications
4
51
2
Order By: Relevance
“…This discrepancy in the time course of SBC neuroprotection measured for histopathology versus neurobehavioral deficits is intriguing, but not necessarily counterintuitive. Studies of brain trauma and ischemia have repeatedly shown that neurofunctional recovery may involve integrated compensatory abilities of the brain in the absence of focal neuronal survival (Dixon et al, 1998;Lu et al, 2009). In this study, the protective effects of SBC on acute postinjury FIG.…”
Section: Discussionmentioning
confidence: 78%
“…This discrepancy in the time course of SBC neuroprotection measured for histopathology versus neurobehavioral deficits is intriguing, but not necessarily counterintuitive. Studies of brain trauma and ischemia have repeatedly shown that neurofunctional recovery may involve integrated compensatory abilities of the brain in the absence of focal neuronal survival (Dixon et al, 1998;Lu et al, 2009). In this study, the protective effects of SBC on acute postinjury FIG.…”
Section: Discussionmentioning
confidence: 78%
“…Experimental and clinical efforts aimed at treating this significant health care issue have resulted in numerous therapeutic approaches such as, but not limited to, anti-inflammatory and anti-oxidative strategies [4,34,36,39,51,56,101], hypothermia [5,9,13,14,21,57], and the exogenous administration of neurotrophins [19,84,88]. Another line of research that has received significant attention as a potential treatment strategy is the administration of various pharmacologic agents targeting both specific and non-specific neurotransmitter systems in an attempt to restore neural activity that has been altered by TBI [2,25,44,[51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Several clinical and experimental studies have shown the neuroprotective effects of mild-to-moderate hypothermia, including inhibition of neurological injury, reduction of infarct size, and improvement of neurological outcome. [15][16][17][18] In our previous studies, we found that post-traumatic moderate hypothermia significantly attenuated cell death within the hippocampus after fluid percussion TBI. 3 However, precise mechanisms underlying this phenomenon are still unclear.…”
Section: Introductionmentioning
confidence: 87%